Soil carbon stock and physico-chemical properties in important plantations of Tamil Nadu, India - Prabha, A. C. Surya; Rajkamal, A.; Senthivelu, M.; Pragadeesh, S. (International Journal of Environment, Agriculture and Biotechnology, 2022)
Soil organic carbon (SOC) plays an important role in soil fertility and is of paramount importance for its contributions to mitigation and adaptation to climate change. The present study was undertaken to estimate the SOC stock and soil properties in important plantations of the Southern zone in Tamil Nadu. Four different species were selected for the study viz, Eucalyptus, Casuarina, Melia and Teak. In all the plantations selected for estimation of biomass, composite soil samples were collected at three different depths; i.e., 0-15, 15- 30 and 30-45 cm. The soil samples were analysed for the carbon stock and various properties such as pH, Electrical conductivity, Organic carbon, Available N, Available P, Available K. Among Eucalyptus plantations, clonal plantation of >6 years sequestered the highest amount of soil carbon (19.8 Mg ha-1) at 30 cm depth. SOC stock was maximum in Casuarina plantation of > 5 years (23.3 Mg ha-1). Among the different Melia plantations, maximum SOC stock was observed in Melia plantation of 5 to7 years old (15.6 Mg ha-1), and in Teak plantations, SOC stock was highest in plantations of > 15 years old (22.1 Mg ha-1). The soil pH and Electrical conductivity significantly differed among the plantations and decreased with an increase in the age of plantation. Nitrogen availability was highest (303.98 kg ha-1 ) in >5 years of Casuarina clonal plantation at 0-15 cm depth. Among the plantations the available potassium was high in surface soils (0-15 cm) of >5 years Casuarina clonal plantation (329.50 kg ha-1). The data generated in the present study would provide valuable information on the scope of afforestation and reforestation projects for sustaining the livelihoods of the farming community and also will encourage them to contribute to mitigating global carbon emissions and expanding forest and tree cover.